Correction of stress-induced changes of the activity of the gene of ultraearly response c-fos in the lateral large-cell subnuclei of the paraventricular nucleus of the rat hypothalamus - Bulyk R.Y. (Морфологія, 2009)
The author has studied the effect of melatonin and a synthetic bioregulator – epithalon for the purpose of correction stress-induced changes of the activity of the gene of “ultraearly response” c-fos in the lateral large cell subnuclei of the paraventricular nucleus of the rat hypothalamus at different intervals of 24-hour period (in the daytime and at night). The expression of the product of this gene – protein c-fos in animals kept under normal conditions of alternating illumination and darkness demonstrated a clear-cut circadian pattern (with a higher level by day). The diurnal index of the c-fos content in the animal lateral large cell subnuclei of the paraventricular nucleus is lower by 33,0%, under conditions of light stress, whereas the nocturnal one approximated to the control values. An injection of melatonin (0,5 mg/kg) to light-stressed animals re-flected at 02.00 p.m. hundred by exceeding the index of the c-fos protein in the animal lateral large cell subnuclei of the paraventricular nucleus almost two fold compared to the experimental findings on stressed animals without hormone intro-duction, as well as by a normalization of the circadian dynamics of the expression of the gene under study. An augmentation of the index of the c-fos protein concentration was disclosed in the structure upon using tetrapeptide epithalon (0,5 mkg/kg) at night in relation to individuals with epiphysial hypofunction without undergoing experimental therapy with epithalon. No such effect was fixed at night.